The Art of Management of Children with Steroid-Resistant and Cyclophosphamide-Resistant Nephrotic Syndrome in Indonesia - Widiasta, Ahmedz; Ilman, Muhammad; Rachmadi, Dedi (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
Background: Steroid resistant nephrotic syndrome (SRNS) in Indonesia contributes to chronic kidney disease (CKD). Method: Data from several teaching hospitals in Indonesia states that the incidence of CKD which originates from inadequate therapy nephrotic syndrome and steroid resistant nephrotic syndrome is around 60 – 70%. Result: This figure is much higher than in developed countries. One of the causes is that the main treatment for SRNS is with a calcineurin inhibitor, namely cyclosporin A, which is not yet available. This case report discuss the management of SRNS with cyclosporine A as an effort to prevent CKD at one of the provincial referral hospitals in Indonesia. Conclusion: Administration of CyA is the therapy of choice for SNRS, because it has a higher remission rate than CPA. The speed of achieving remission was also higher in CyA than CPA. There are several obstacles in providing CyA to pediatric SNRS patients in Indonesia currently, the main obstacle is cost. Keywords: Children; Chronic Kidney Disease ;  Steroid Resistant Nephrontic Syndrome; Intensive Care; Cyclosporine